Nano urea’s environmental edge and economic efficacy in boosting wheat grain yield across diverse Indian agro-climates - S. C. Tripathi; Nitesh Kumar; Karnam Venkatesh (Scientific Reports)
Abstract The gradual increase in the consumption of mineral nitrogen is leading to heightened levels of harmful air pollutants, particularly N2O emissions from the agriculture sector. A potential solution to address the issues arising from the excessive use of urea in wheat is the substitution of conventional urea with nano urea. This study aimed to quantify the effects of nano urea, both independently and in conjunction with prilled urea, under various agroclimatic and sowing conditions in India. To achieve this objective, a multi-location field experiment on nano and prilled urea was conducted under irrigated conditions across 21 locations with 13 different treatments during the agricultural seasons of 2021–2022 and 2022–2023. The experiments followed a randomized block design with three replications, covering diverse agro-climatic regions of India. Analysis of combined data from multiple years and locations revealed that applying the recommended dose of nitrogen (RDN), i.e., 150 kg/ha in NWPZ (North western plains zone) and NEPZ (North eastern plains zone), and 120 kg/ha in CZ (Central zone) and PZ (Peninsular zone), along with two sprays of nano urea, resulted in a significant increase in grain yield 7.6%, 8.0%, 5.5%, and 9.1% in NWPZ, NEPZ, CZ, and PZ, respectively, compared to RDN alone. Notably, using 75% RDN along with either two sprays of nano urea or 5% urea showed a non-significant (P ≥ 0.05) difference in grain yield compared to the full RDN. From the perspective of higher net benefits, the combination of RDN and two sprays of 5% urea emerged as the most favourable option. On the other hand, considering the higher marginal rate of return (MRR), the combination of 75% RDN and two sprays of 5% urea proved to be more advantageous for farmers across the zones. In conclusion, environmentally friendly practices such as two sprays of nano urea or 5% urea combined with 75% RDN present promising alternatives for Indian farmers seeking to enhance wheat grain yield. Thus, this practice can save 25% of nitrogen (1.02 billion kg) which can reduce 5.06 billion kg CO2 equivalent emissions annually over recommended practice and can play a significant role in achieving the goal of net zero emissions by 2070 in India.